2015
DOI: 10.1099/vir.0.000166
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel nidovirus in cattle with respiratory disease

Abstract: The family Coronaviridae represents a diverse group of vertebrate RNA viruses, all with genomes greater than 26 000 nt. Here, we report the discovery and genetic characterization of a novel virus present in cattle with respiratory disease. Phylogenetic characterization of this virus revealed that it clusters within the subfamily Torovirinae, in the family Coronaviridae. The complete genome consists of only 20 261 nt and represents the smallest reported coronavirus genome. We identified seven ORFs, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…Though toroviruses mainly associate with enteric diseases, recent studies have shown that they can be both entero-and pneumotropic (31,55,56). New nidoviruses were recently identified in the lungs of cattle and wild shingleback lizards with pneumonia, though their direct association with disease has so far not been examined (31,37). We found MVNV-associated lesions almost exclusively in the airways and lungs, similar to previous reports on nidovirus infections in other python species (8,9,15).…”
Section: Fig 10supporting
confidence: 88%
See 2 more Smart Citations
“…Though toroviruses mainly associate with enteric diseases, recent studies have shown that they can be both entero-and pneumotropic (31,55,56). New nidoviruses were recently identified in the lungs of cattle and wild shingleback lizards with pneumonia, though their direct association with disease has so far not been examined (31,37). We found MVNV-associated lesions almost exclusively in the airways and lungs, similar to previous reports on nidovirus infections in other python species (8,9,15).…”
Section: Fig 10supporting
confidence: 88%
“…6). Further, the python nidoviruses clustered together with shingleback nidovirus (GenBank accession number KX184715) (37), Xinzhou nematode virus 6 (GenBank accession number KX883637), Xinzhou toro-like virus (NCBI reference sequence accession number NC_033700), and bovine nidovirus (NCBI reference sequence accession number NC_027199) (31). Consistent with the previous reports, these form a clade that is separate from both the genus Bafinivirus and the genus Torovirus (Fig.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The order nidovirales compromises divergent virus families with notable human and animal pathogens like for example severe acute respiratory syndrome (SARS) coronavirus and porcine reproductive and respiratory syndrome virus (PRRSV) [13]. The snake nidoviruses were assigned to the family coronaviridae in the subfamily torovirinae that covers two genera: torovirus and bafinivirus infecting mammals and fish, respectively [14][15][16][17]. The reptile nidoviruses cluster together in a monophyletic clade and a new genus for these unassigned viruses was proposed: barnivirus (bacilliform reptile nidovirus) [4].…”
Section: Introductionmentioning
confidence: 99%
“…This order previously contained four family-level groups, the Coronaviridae which infect birds and mammals including humans, the Arteriviridae which infect non-human mammals, the Mesoniviridae which infect arthropods, and the Roniviridae which infect crustaceans (Lauber et al, 2013). However, recent papers (Lauck et al, 2015;O'Dea et al, 2016;Saberi et al, 2018;Shi et al, 2018Shi et al, , 2016Tokarz et al, 2015;Vasilakis et al, 2014;Wahl-Jensen et al, 2016) and our results (see below) have added to within-family diversity and revealed several highly divergent nido-like viruses which the Nidovirales Study Group proposed, pending ICTV ratification, to form four new virus families within the Nidovirales (Gorbalenya et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%